Laying behaviour of chicken as influenced by litter, nest type and nesting materials - Islam, M S; Howlider, M A R; Biswas, M A A; Islam, M S (The Indian Journal of Animal Sciences, 2012)
Interaction of floor litter, nest type and nesting materials on the time spent in laying, time of oviposition, incidence of floor laying and egg breakage were investigated in RIR and White Leghorn (WLH) birds. Irrespective of breed, the hens which laid heavier eggs preferred single storied (SS) to double storied (DS) nest. The RIR took more time to lay in rice husk (RH) littered pens, than that in saw dust (SD) littered pens. The RIR spent more time to lay in upper tier than in lower tier, which was not true for WLH. There was significant interactions of breed nest type, floor litter and nesting materials to influence site selection for laying and time spent in laying. Floor laying and egg breakage were higher for RIR than those for WLH. Floor laying was higher in SD littered pen, whereas egg breakage was higher in RH littered pens.